Precipitation Modeling and Quantitative Analysis - Li, Xiaofan; Gao, Shouting; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
The book examines surface rainfall processes through cloud-resolving modeling and quantitative analysis of surface rainfall budget and summarizes modeling and analysis results in recent seven years. The book shows validation of precipitation modeling against observations and derives a set of diagnostic precipitation equations. The book provides detailed discussions of the applications of precipitation equations to the examination of effects of sea surface temperature, vertical wind shear, radiation, and ice clouds on torrential rainfall processes in the tropics and mid-latitudes, and to the studies of sensitivity of precipitation modeling to uncertainty of the initial conditions and to the estimate of precipitation efficiency. The book can be used as a text book for graduate students and will be beneficial to researchers and forecasters for precipitation process studies and operational forecasts. Xiaofan Li is a physical scientist at the Center for Satellite Applications and Research, National Environmental Satellite, Data, and Information Service, National Oceanic and Atmospheric Administration, Camp Springs, Maryland, USA. He has a doctorate in meteorology from the University of Hawaii at Manoa, Honolulu, USA and a master$1 (Bs degree in meteorology from Nanjing University of Information Science and Technology, Nanjing, China. Shouting Gao is a professor at the Laboratory of Cloud-Precipitation Physics and Severe Storm, Institute of Atmospheric Physics, Chinese Academy of Sciences, Beijing, China. He has a doctorate and a master$1 (Bs degree in meteorology from the Institute of Atmospheric Physics, Beijing, China.s
-Precipitation Modeling with Cloud-Resolving Model -- -Precipitation Equations and Process Analysis -- -Tropical Precipitation Processes -- -Effects of Sea Surface Temperature -- -Effects of vertical wind shear -- -Microphysical and Radiative Effects of Ice clouds -- -Cloud Radiative Effects -- -Precipitation Efficiency -- -Sensitivity of Precipitation Modeling to Uncertainty of Initial Conditions.
Keywords: Geography; Meteorology; Geology; Computer simulation; Earth Sciences; Meteorology/Climatology.; Natural Hazards; Simulation and Modeling